Kingston the great dane ebook - Florence, Debbi Michiko (My Furry Foster Family., 2020)
What do you do with a gentle Great Dane who's the size of a cow but acts like he's no bigger than a mini dachshund? If you're eight-year-old Kaita Takano and her animal-fostering family, you shower the dog with love and do everything you can to find him a forever home. Sweet-natured illustrations and Kaita's first-person narration pair up for plenty of chapter book fun.